Upaya Hukum untuk Menjerat Tindakan Pelakor dalam Perspektif Hukum Adat Dayak Ngaju - Putri Fransiska Purnama Pratiwi; Suprayitno Suprayitno; Triyani Triyani (University of Merdeka Malang, 2019)
The problem that occurs is a legal vacuum regarding the regulation of sanctions that can be imposed on women who dare to tempt married men (Pelakor) through national law. In Dayak indigenous people in Central Kalimantan, the Dayak Customary Law is enforced firmly, but is still not widely known. This research uses a type of qualitative empirical research, conducted by visiting the Kedamangan Institutions in Central Kalimantan and Dayak Customary Council (DAD) in Central Kalimantan. It can complement the national legal effort before the national legal implementation of RUU KUHP for Dayak Ngaju community in Central Kalimantan. The legal effort taken to ensnare the cheating woman’s action is the challenge of oath that is the most serious legal effort that can be conducted by the indigenous people of Dayak Ngaju tribe. They believe that the oath pronounced during the Basara Adat will be seriously for those who dare to lie.They might have a short life, no fortune and suffer from continuing illness for themselves and their descendants and siblings. Dayak Ngaju’s custom sanctions imposed for Pelakor is to pay twice the value of the customary marriage (dowry) of a man he arrogated to pay shame compensation for the woman's wife's legal family, pay compensation for the marriage costs for the legal wife and pay for the party peace.How to cite item: Pratiwi, P., Suprayitno, S., Triyani, T. (2019). Upaya Hukum untuk Menjerat Tindakan Pelakor dalam Perspektif Hukum Adat Dayak Ngaju. Jurnal Cakrawala Hukum, 10(2), 209-217. doi:https://doi.org/10.26905/idjch.v10i2.3469